Quality Of Service, Patient Safety, and Patient Trust in Patient Loyalty - Abbas, Fatimah; Ansar; Malik, Tajuddin (Cendekiawan Indonesia Timur, 2023)
The services in question are health services that are fast, precise, cheap, and friendly. With the increasing safety of hospital patients, public trust in hospital services is also hoped to increase. Patient safety is a top priority to be implemented related to the issue of quality and hospital image. This kind of research is known as descriptive qualitative research, and rather than being reported in the form of statistics, the findings are described verbally and shown visually. A technique of study known as qualitative research gathers descriptive data from persons in the form of written or spoken words and data collected by watching their behavior. Understanding different data-collection tactics enable researchers to get data, assuming that the strategy displays an abstract. It is not feasible to physically materialize it into objects that can be seen, yet, it is possible to demonstrate it via their application. The results show that implementing quality services is very important in this era of competition. The higher the service quality, the more satisfied service recipients will be. Service quality in this era is an essential factor and is one of the keys to competitive advantage in marketing. Service quality can be used to measure customer satisfaction with the company. Improving the quality of health services, service quality, and patient satisfaction are indicators of service delivery success in hospitals.